OP0108 Inhibition of radiographic progression in psoriatic arthritis by adalimumab independent of the control of clinical disease activity. (15th June 2017) - Landewé, R; Ritchlin, CT; Coates, LC; Aletaha, D; Guérette, B; Zhang, Y; Ganz, F; Hojnik, M
Abstract : Background: Patients (pts) with psoriatic arthritis (PsA) may experience structural damage and irreversible functional impairment if not treated appropriately. Treatment with TNF inhibitors in rheumatoid arthritis (RA) pts showed inhibition of radiographic progression larger than expected based on the control of clinical disease activity. 1 Preliminary results showed that such a disconnect phenomenon may also be observed in PsA pts following treatment with adalimumab (ADA). 2 Objectives: The objective of this analysis was to further examine the relationship between inhibition of radiographic progression and control of clinical disease activity using different disease activity measures following treatment with originator ADA versus placebo (PBO) in pts with active PsA. Methods: ADEPT 3 was a 24-week (wk), randomized, double-blind trial comparing the safety and efficacy of ADA with PBO in pts with active PsA. In this post hoc analysis, radiographic progression, defined as change from baseline (BL) to wk 24 in modified total Sharp score (ΔmTSS) >0.5, was calculated in pts with evaluable radiographs at both time points. Pts were classified based on achieving minimal disease activity (MDA) and different subcategories of disease activity (remission, low, moderate, or high) based on time-averaged (TA) DAS28(CRP), DAPSA, and PASDAS. The associations between ΔmTSS and disease activity were assessed by Pearson ( r p ) or Phi ( r φ ) correlation coefficients. Results: Of the 296 pts (ADA, N=144; PBO, N=152) included in this analysis, higher proportions of pts receiving ADA compared with PBO achieved MDA and remission/low disease activity status across all the outcome measures. There was a significant interaction between treatment and disease activity status with respect to radiographic progression (P<.001 for all outcome measures). In addition, treatment with ADA for 24 wks compared with PBO resulted in significantly lower mean ΔmTSS even in pts with moderate or high disease activity (TA-DAPSA or TA-PASDAS) or not achieving MDA (Table). Radiographic progression showed a weak, but significant correlation with disease activity status in pts treated with PBO ( r p ≥0.3, P<.001 for TA-DAS[CRP], TA-DAPSA, and TA-PASDAS; r φ = –0.14 [95% CI:–0.20 to –0.09 for MDA), but not ADA. Conclusions: The results showed that the relationship between disease activity as determined by various outcome measures differed between ADA and PBO treated pts. ADA provided inhibition of radiographic progression which was somewhat larger and independent of the control of clinical disease activity. This supports the disconnect phenomenon in PsA following ADA treatment. References: Landewé R, et al. Arthritis Rheum. 2006; 54:3119–25. Mease PJ, et al. Arthritis Rheum. 2010; 62 (suppl 10). Mease PJ, et al. Arthritis Rheum. 2005; 52:3279–89. Acknowledgements: AbbVie funded the study (NCT00646386 ), contributed to its design, and participated in data collection, analysis and interpretation of the data, and in writing, review, and approval of the publication. Medical writing support was provided by Deepa Venkitaramani, PhD, of AbbVie. Disclosure of Interest: R. Landewé Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB and Wyeth, Consultant for: Abbott/AbbVie, Ablynx, Amgen, Astra-Zeneca, BMS, Janssen (formerly Centocor), GSK, Merck, Novo-Nordisk, Novartis, Pfizer, Roche, Schering-Plough, TiGenics, UCB, and Wyeth; is Director of Rheumatology Consultancy BV, Speakers bureau: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB and Wyeth, C. Ritchlin Grant/research support from: Amgen, Janssen, Pfizer, and UCB, Consultant for: AbbVie, Amgen, Janssen, Lilly, Pfizer, and UCB, L. Coates Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, and UCB, Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, and UCB, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, and UCB, D. Aletaha Grant/research support from: AbbVie, BMS, Janssen, Lilly, Merck, Medac, Mitsubishi/Tanabe, Pfizer, Roche, and UCB, Consultant for: AbbVie, BMS, Janssen, Lilly, Merck, Medac, Mitsubishi/Tanabe, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, BMS, Janssen, Lilly, Merck, Medac, Mitsubishi/Tanabe, Pfizer, Roche, and UCB, B. Guérette Shareholder of: AbbVie, Employee of: AbbVie, Y. Zhang Shareholder of: AbbVie, Employee of: AbbVie, F. Ganz Shareholder of: AbbVie, Employee of: AbbVie, M. Hojnik Shareholder of: AbbVie, Employee of: AbbVie